LINGUISTIC INTERPRETATION OF EUPHEMISMS USING FOLK PROVERBS - Yuldashevna, Ibragimova Zamira (Journal of Higher Education and Academic Advancement, 2024)
This article focuses on the linguistic and cultural significance of euphemisms used in folk proverbs and the etymology of their origin